Infantile epileptic spasms syndrome as an initial presentation in infantile choroid plexus papilloma: A case report - Zhou, Faliang; Li, Yu; Shen, Lixue; Yao, Hongxin; Hou, Xinlin (Frontiers in Pediatrics, 2022)
We present an interesting report of a 5 months old infant with epileptic spasms and developmental delay who presented with non-isolated ventriculomegaly in utero and whose brain magnetic resonance imaging revealed right ventricular choroid plexus papilloma (CPP). The epileptic spasms persisted even with the use of antiepileptic therapies but was apparently cured after the removal of a CPP.